Upaya Meningkatkan Hasil Belajar Siswa Pada Materi Himpunan Dengan Model Pembelajaran Reciprocal Teaching - eka suryani Rindani; adek nila sari harahap; Nurdalilah (Program Studi Matematika Universitas Graha Nusantara Padangsidimpuan, 2023)
This research is classroom action research (PTK). The learning tools used in this research are the Learning Implementation Plan (RPP), Student Activity Sheet (LAS), test instruments, student activity observation sheets and teacher ability observation sheets to manage learning. The results of the research showed that by applying the Reciprocal Teaching learning model in cycle I, the percentage of completeness in the minimum